1995
DOI: 10.1007/bf03226370
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and metabolite pharmacokinetics of BRB-I-28, a class Ib antiarrhythmic agent

Abstract: The metabolism of BRB-I-28 (7-benzyl-3-thia-7-azabicyclo[3.3.1]nonane), a novel class Ib antiarrhythmic agent, was characterized in vivo in dogs and rats and in vitro with rat liver microsomal preparations containing a NADPH-generating system. In dogs, rats and the in vitro hepatic microsomal oxidation system, BRB-I-28 was extensively metabolized to form 7-benzyl-3-thia-7-azabicyclo [3.3.1]nonane-3-oxide (I), a major metabolite. The metabolite I was produced via S-oxidation, presumably by the hepatic P-450 sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…An appropriate pharmacokinetic model was chosen based on the lowest Akaike’s information criterion (AIC) value, lowest weighted squared residuals, lowest standard errors of the fitting parameters, and dispersion of the residual under equal weight scheme [2527]. All the data were expressed as the mean ± standard deviation and the levels of statistical significance were assessed using Student t test.…”
Section: Methodsmentioning
confidence: 99%
“…An appropriate pharmacokinetic model was chosen based on the lowest Akaike’s information criterion (AIC) value, lowest weighted squared residuals, lowest standard errors of the fitting parameters, and dispersion of the residual under equal weight scheme [2527]. All the data were expressed as the mean ± standard deviation and the levels of statistical significance were assessed using Student t test.…”
Section: Methodsmentioning
confidence: 99%
“…All incubation mixtures contained the following ingredients (a modified procedure of Chen et al, 1995Chen et al, , 1999b at the indicated final concentrations (200 l): 1ϫ PBS, microsomes (1 mg/ml), glucose 6-phosphate (10 mM), glucose-6-phosphate dehydrogenase (2 units/ml), and MgCl 2 (5 mM). The mixtures were preincubated at 37°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…An appropriate pharmacokinetic model was chosen based on the lowest Akaike's information criterion (AIC) value, the lowest weighted squared residuals, the lowest standard errors of the fitting parameters, and the dispersion of the residual under an equal weight scheme (Chen et al, 1995(Chen et al, , 2001a(Chen et al, ,b, 2002Gabrielsson and Weiner, 1997). The area under the curve (AUC) was calculated by the trapezoidal rule between the first (0 h) and last (8 h) sampling time plus C n / n , where C n is the concentration of last sampling, and n is the elimination rate constant (Zhang et al, 2006).…”
Section: Pharmacokinetics Analysismentioning
confidence: 99%